Analysis Of Return On Assets And Dividend Payout Ratio On Stock Performance: Case Study of Pharmaceutical Companies Listed on the Indonesian Stock Exchange for the 2017-2022 Period - Muktiadji, Nusa; Amanda, Beautiful Dinda; Khim, Soei (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the Analysis of Return on Assets and Dividend Payout Ratio on Stock Performance (Case Study of Pharmaceutical Companies Registered on the Indonesia Stock Exchange for the 2017-2022 period). The population in this study were 12 pharmaceutical companies listed on the IDX and 6 samples. Companies with 6 years of data. The sampling method used is the non-random sampling method. The data analysis method used is multiple linear regression analysis to determine the effect of profitability, market ratios and interest rates on stock prices. Testing data was carried out using IBM SPSS Statistics 25 Software. From the results of the regression analysis test, it is obtained that the t value is - 2.049 with a significance level of 0.048 (0.048 <0.05) so that the variable Return on Assets (X1) has a significant effect on stock prices, which means H1 is acceptedFrom the results of the regression analysis test, it was obtained that the t value was 1.478 with a significance level of 0.149 (0.149 > 0.05), so the dividend payout ratio (X2) variable did not significantly affect stock prices, which means H2 was rejected. From the results of the regression analysis test, the calculated f value was obtained. of 3.631 with a significance level of 0.038 (0.038 <0.05) then the variables Return on Assets and Dividend Payout Ratio have a simultaneous and significant effect on stock prices, which means H3 is accepted. Keywords : Profitability, Market Ratio, Stock Prices